Program Inovasi Inovasi CERDAS (Cegah Risiko Digital Anak Sejak Dini) melalui Sosialisasi dan Pendampingan Orang Tua dalam Mengelola Screen Time - Yustanta, Brivian Florentis; Ivantarina, Dintya; Betty Mulyati , Sesaria (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2026)
The development of digital technology provides easy access to information, but on the other hand, it has an impact on increasing excessive screen time exposure in early childhood. This exposure has been proven to affect growth and development, especially in children's cognitive, social emotional, and physical aspects. This phenomenon is increasingly worrying in Indonesia, including in Kediri Regency, where gadget use from an early age is increasing without adequate supervision. Parents' lack of understanding about digital risks and screen time management exacerbates this condition. This program is designed as a community engagement activity based on education and intensive mentoring for parents of children aged 3–10 years. The methods used are interactive outreach, focus group discussions (FGDs), and mentoring on screen time management practices at home for two weeks. The main target group is 45 families in the working area of ​​the Pare Community Health Center, Kediri. After the program implementation, there was a significant increase in parental knowledge about screen time management (the mean score increased from 56 to 85, p<0.05). In addition, there was a 30% decrease in average screen time for children within four weeks, as well as an increase in active supervision practices for children while using devices. These results demonstrate that educational interventions and parental guidance are effective strategies for fostering healthy digital parenting patterns. Good knowledge coupled with hands-on practice helps parents manage their children's screen time and prevent long-term negative impacts. The CERDAS program has proven effective as a community service innovation in improving family digital literacy and protecting children from digital risks from an early age. Similar programs are needed for replication in other regions, as well as integration into integrated health service post (Posyandu) programs for toddlers.